2020
DOI: 10.1002/cncy.22325
|View full text |Cite
|
Sign up to set email alerts
|

Innovations: Innovating together while social distancing

Abstract: Her areas of research and expertise are cytopathology and surgical pathology of the head and neck and endocrine systems, with particular interest in thyroid nodules, ultrasound-guided fine-needle aspiration, and novel applications of social media for medical professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…This tool could help to discuss and even solve some difficult cases. [12][13][14] Therefore, the more pathologists and related professionals meet and interact with each other, the better.…”
Section: Y Tology In So Cial Ne T Work S: a S Trong And Vis Ib Le Com...mentioning
confidence: 99%
See 1 more Smart Citation
“…This tool could help to discuss and even solve some difficult cases. [12][13][14] Therefore, the more pathologists and related professionals meet and interact with each other, the better.…”
Section: Y Tology In So Cial Ne T Work S: a S Trong And Vis Ib Le Com...mentioning
confidence: 99%
“…With the existence of an online community, the creation of professional profiles enables one to connect with experts in any field from all over the world and collaborate in international research groups. This tool could help to discuss and even solve some difficult cases 12–14 . Therefore, the more pathologists and related professionals meet and interact with each other, the better.…”
Section: Cytology In Social Network: a Strong And Visible Communitymentioning
confidence: 99%
“…Engaging with SoMe platforms offers a valuable opportunity for the lower impact journals to gain broader visibility to reach beyond the traditional academic circle. 24 This allows enhanced accessibility and knowledge dissemination, ultimately contributing to increasing citation rates, which can positively influence journals' impact factor.…”
Section: National and International Cytopathology Journals In Somementioning
confidence: 99%
“…Furthermore, the study demonstrated that Twitter activity was independent of the journal impact factor; contrary to expectation, articles from “highest impact” journals did not necessarily attract the most online discussion. Engaging with SoMe platforms offers a valuable opportunity for the lower impact journals to gain broader visibility to reach beyond the traditional academic circle 24 . This allows enhanced accessibility and knowledge dissemination, ultimately contributing to increasing citation rates, which can positively influence journals' impact factor.…”
Section: Introductionmentioning
confidence: 99%